Strategic informative advertising in a tv-advertising duopoly - Tore Nilssen; Lars Sørgard (University of Oslo, Department of Economics, 2000)
We consider a model of strategic informative advertising where the advertising is done on TV and where the TV channels' advertising prices are endogenously determined. We discuss how these prices, and the advertising firms' advertising efforts, vary with the two key parameters of the model: the degree of product differentiation in the product market and a measure of the relative sizes of the TV channels' viewer bases. We find, in particular, that the larger the size difference among the TV channels is, the higher is the advertising price, and thus the less advertising is done.
Keywords: L82; M37; 330; Television industry; Advertising; Werbeplanung; Fernsehwerbung; Kosten; Duopol; Theorie